KARAKTERISTIK SURAT TILANG DALAM PENINDAKAN PELANGGARAN LALU LINTAS DAN ANGKUTAN JALAN - Jemmy Jefry Pietersz (Faculty of Law, Universitas Pattimura, 2010)
Violations action in the field of Traffic and Transportation is the act of sanctioning violations. This action is done by issuing Surat Tilang as a result of the violations found in the inspection of motor vehicles on the road. Surat Tilang has characterized as a unilateral administrative action as a form of administrative sanctions against violations committed and does not require the court rulings against government actions that are unilateral. Thus, the Surat Tilang is categorized as an Administrative Decision.